Potential Drug-Drug Interactions in Critically Ill Medical Patients: A Cross-Sectional Study - Elham Hosseini; Lida Shojaei; Hassanali Karimpour; Foroud Shahbazi (Research Center for Rational Use of Drugs (RCRUD), 2019)
Background:  Drug interaction commonly occurred in critically ill patients and may increase hospital lengths of stay and total cost. The aim of the present study is to evaluate potential drug-drug interaction in critically ill patients. Methods: In this cross-sectional study, medical records of critically ill patients admitted to the 16-bed intensive-care units of a teaching hospital were assessed according to the Micromedex® drug interaction and drug interaction fact®. The identified drug-drug interactions were categorized by level of severity. The agreement between two resources was assessed. Results: Our survey found 915 and 564 paired DDIs according to the Micromedex® and drug interaction fact®, respectively, amongst 120 patients.  The prevalence of potential DDIs (pDDIs) was 87.7% and 91.7% with drug interaction Fact® and Micromedex®, respectively. Approximately, 80% of recruited patients, had at least three pDDIs based on Micromedex®. A significant moderate agreement between two drug interaction compendia was reported. (kappa= 0.41, 95% CI: 0.167-0.649, p<0.001). The serotonin syndrome, increasing the risk of bleeding and hyperkalemia were the major possible consequence of potential DDIs; but none of them occurred. Conclusions: Most of the observed interactions were mild to moderate in nature. However, major and contraindicated interactions are possible in critically ill patients. Therefore, monitoring of patients with possible major or contraindicated drug interaction is recommended.